Luminous exposures and light-fastness survey in daylit historical museum galleries under tropical sky conditions - Ahmad, Noraini; Sh Ahmad, Sabarinah; Talib, Anuar (Trans Tech Publications Ltd., Switzerland, 2012)
This paper highlights the results of light levels and light-fastness study conducted in four daylit historical museum galleries in Malaysia. These museums architectural features allow sun radiation into the building, causing light exposure damage to artifacts. This study aims to evaluate the luminous exposures and light-fastness as an initial preventive conservation measure in daylit historical museum galleries under the tropical sky conditions. Light sensors with data-loggers and Light-fastness dosimeters were installed throughout the museums to take cumulative light exposure measurements during museum opening hours. Both instrumentations were tested in the field during different campaigns exposures. After exposures between 90 and 100 days, these dosimeters showed photo-induced colour changes which translated exposures into equivalent luminous exposure and estimated annual exposures (Lux hours) which were used to validate the measured values of illuminance data. Simulated light dosimeters and measured illuminance data show good correlation. Thus, equivalent light dosimeter makes sense to assess the impact of light distributions.